2018
DOI: 10.1002/acn3.541
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase‐5 inhibition potentiates cerebrovascular reactivity in chronic traumatic brain injury

Abstract: BackgroundTraumatic cerebrovascular injury (TCVI), a common consequence of traumatic brain injury (TBI), presents an attractive therapeutic target. Because phosphodiesterase‐5 (PDE5) inhibitors potentiate the action of nitric oxide (NO) produced by endothelial cells, they are candidate therapies for TCVI. This study aims to: (1) measure cerebral blood flow (CBF), cerebrovascular reactivity (CVR), and change in CVR after a single dose of sildenafil (ΔCVR) in chronic TBI compared to uninjured controls; (2) exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 41 publications
6
23
1
Order By: Relevance
“…Although CVR deficit is a symptom of many neurodegenerative diseases, 23,54,55 recent work by Diaz-Arrastia et al 7,17,56,57 has demonstrated global, Figure 7. ELISA measurement of aSMA concentration in cortical vascular-enriched fractions at three months and nine months post-injury.…”
Section: Discussionmentioning
confidence: 99%
“…Although CVR deficit is a symptom of many neurodegenerative diseases, 23,54,55 recent work by Diaz-Arrastia et al 7,17,56,57 has demonstrated global, Figure 7. ELISA measurement of aSMA concentration in cortical vascular-enriched fractions at three months and nine months post-injury.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that acute TMBs are associated with acute MRI diffusion-weighted changes like those well-described from acute stroke studies. Thus, we postulate that TMBs may be useful biomarkers for identifying TBI patients that may benefit in the acute phase from therapies aimed at minimizing acute ischaemic damage, or in the chronic phase, at improving microvascular cerebral blood flow (Zhang et al, 2006;Kenney et al, 2018). The persistence of inflammatory cells triggered by these TMBs in the perivascular spaces may also impede fluid movement, which, if in humans is analogous to the glymphatic system critical for removing substrates from the brain as described in rodents (Glushakova et al, 2014), may affect the build-up of substrates and lead to secondary injury in humans as well.…”
Section: Discussionmentioning
confidence: 99%
“…TMBs may also serve as biomarkers for patients more likely to have these glymphatic flow system disruptions, facilitating the identification of appropriate patients for therapeutic clinical trials. For example, pharmacological agents suggested by other TBI investigators to act on the microvasculature to increase cerebral perfusion include sildenafil (Kenney et al, 2018) and beta blockers such as propranolol (Loftus et al, 2016). In contrast, minocycline has the potential to reduce acute ischaemic injury through its effects on inflammation, blood-brain barrier, and oedema (Mizuma and Yenari, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Sildenafil has been shown to increase CVR specifically within regions with decreased CVR in chronic TBI subjects. 33,59 This suggests CVR may be a useful biomarker to monitor response to therapy as well. These findings highlight the need for further study of traumatic vascular injury as distinct endophenotype of TBI.…”
Section: Discussionmentioning
confidence: 99%